The Dynamic Interplay of Societal Values, Entrepreneurial Abilities and Skill Sets in Shaping and Propelling Entrepreneurial Activity Among South African Higher Learning Students - Iwu, Chux Gervase; Maziriri, Eugine Tafadzwa; Yu, Derek; Ayandibu, Ayansola (International Review of Management and Marketing, 2024)
The primary aim of this study is to investigate how entrepreneurial abilities and societal values impact the entrepreneurial activity of students. By delving into these dynamics, valuable insights into the factors that drive entrepreneurial activity are provided. This research is specifically focused on a South African institution of higher learning, with the intention of providing insights that can be applied to similar educational settings and contribute to the broader discourse on entrepreneurship. The study employed a quantitative approach and was carried out at a comprehensive tertiary educational institution in South Africa. Data was gathered from students through a structured questionnaire. Structural equation modeling (SEM) analysis was used to test the hypothesized model using the Smart PLS software. The results of the structural equation modeling demonstrate a strong and significant positive influence of entrepreneurial abilities/skill sets on entrepreneurial activity. Additionally, societal values on entrepreneurship show a positive but weak significant influence on entrepreneurial activity. Importantly, the results also indicate that societal values on entrepreneurship positively and significantly impact entrepreneurial abilities and skill sets. This research addresses a critical gap by providing detailed insights into the relationships between societal values, entrepreneurial abilities, and entrepreneurial activity in a higher learning context. The practical implications suggest a need for targeted educational interventions, while the theoretical contributions enhance our understanding of the complex dynamics that shape entrepreneurship. This study aligns with the focus and scope of the journal by advancing knowledge in the field of entrepreneurship within educational settings.